Dyserythropoietic anaemia with an intronic GATA1 splicing mutation in patients suspected to have Diamond‐Blackfan anaemia. Issue 1 (10th January 2022) - Kobayashi, Akie; Ohtaka, Ryusei; Toki, Tsutomu; Hara, Junichi; Muramatsu, Hideki; Kanezaki, Rika; Takahashi, Yuka; Sato, Tomohiko; Kamio, Takuya; Kudo, Ko; Sasaki, Shinya; Yoshida, Taro; et al.
Abstract: Diamond‐Blackfan anaemia (DBA) shares clinical features with two recently reported sporadic cases of dyserythropoietic anaemia with a cryptic GATA1 splicing mutation (c.871‐24 C>T). We hypothesized that some patients clinically diagnosed with DBA but whose causative genes were unknown may carry the intronic GATA1 mutation. Here, we examined 79 patients in our DBA cohort, who had no detectable causative genes. The intronic GATA1 mutation was identified in two male patients sharing the same pedigree that included multiple cases with anaemia. Cosegregation of this mutation and disease in multiple family members provide evidence to support the pathogenicity of the intronic GATA1 mutation.